M-learning in the transmission and sustainability of Cantonese opera in KSK Art Crew - He, Shan; Loo, Fung Chiat; Loo, Fung Ying (2015)
Yueju (Cantonese opera), which originated in Southern China, has a long history in the genre of Chinese opera. This study examines how KSK Art Crew sustains this genre in Malaysia and examines the changes in its transmission processes. Past literatures reveal a number of published research monographs and articles on yueju in mainland China and the diasporic Chinese communities in the United States. This study focuses on KSK Art Crew, led by Kam Sin Kiew, and its innovative teaching methods and continuous effort in the sustainability of Cantonese opera in Malaysia. Findings reveal how Kam, the artistic director and founder of KSK Art Crew led new approaches in the teaching of yueju incorporating technological advances, M-learning approach, and pre-recorded music accompaniment that led to aesthetic and pedagogical changes. In addition, how performances were re-contextualized in the form of a dinner-show to adapt to the modern Malaysian audience is discussed.